Antecedents of Overall E-service Quality and Brand Attachment in the Banking Industry - Lakhi, Gul e Rana; Mohamadali, Noor Azizah (SEISENSE Journal of Management, 2020)
Purpose – The study aims to examine the impact of website design, e-fulfillment, e-service and e-security on overall e-service quality and its impact on brand attachment. Design/methodology/approach – Data of 425 respondents was collected from the internet banking industry users through an online survey. Further, PLS-SEM was employed to analyze the data. Findings – Results indicate that the impact of e-security, e- customer service, and e-fulfillment on overall e-customer service quality was supported. In contrast, the impact of website design was not supported. Further, overall, e-service quality also has a significant impact on brand attachment. Originality/value – This study suggested and tested a brand attachment framework for the banking industry to support strategy formulation for managers.